Association of Dysregulated Central Pain Processing and Response to Disease–Modifying Antirheumatic Drug Therapy in Rheumatoid Arthritis. Issue 12 (4th November 2020) - Heisler, Andrew C.; Song, Jing; Muhammad, Lutfiyya N.; Wohlfahrt, Alyssa; Marder, Wendy; Bolster, Marcy B.; Bingham, Clifton O.; Clauw, Daniel J.; Dunlop, Dorothy D.; Neogi, Tuhina; Lee, Yvonne C.
Abstract : Objective: To determine the association between dysregulated central pain processing and treatment response in rheumatoid arthritis (RA). Methods: One hundred eighty‐two participants with active RA were followed up for 12 weeks after starting a disease‐modifying antirheumatic drug (DMARD). To assess central pain processing, participants underwent quantitative sensory testing (QST), including assessment of pressure pain thresholds (PPTs) at the trapezius muscles, temporal summation, and conditioned pain modulation (CPM). QST measures were categorized as high central dysregulation versus low central dysregulation. The association between baseline central dysregulation and treatment response, as defined by the European League Against Rheumatism (EULAR) response criteria, was assessed using multiple logistic regression adjusted for demographic characteristics, RA‐related variables, and psychosocial variables. Results: A good EULAR response was achieved in fewer participants with high CPM dysregulation than participants with low CPM dysregulation (22.5% versus 40.3%; P = 0.01). A similar trend, though not significant, was noted when central dysregulation was assessed with PPT and temporal summation. The adjusted odds ratios (ORs) for the association between high central dysregulation and good EULAR response were 0.59 for PPTs (95% confidence interval [95% CI] 0.28–1.23), 0.60 for temporal summation (95% CI 0.27–1.34), and 0.40 for CPM (95% CI 0.19–0.83). In a model examining the combined effects of dysregulated temporal summation and CPM, dysregulation of both measures was associated with lower odds of achieving a good EULAR response (OR 0.23 [95% CI 0.07–0.73]). Conclusion: Low CPM was significantly associated with lower odds of achieving a good EULAR response, suggesting that inefficient descending inhibitory mechanisms may be a potential treatment target for further study.